Follicular Fluid Growth Factors and Interleukin Profiling as Potential Predictors of IVF Outcomes - Molka, Bouricha; Gwladys, Bourdenet; Dorian, Bosquet; Lucie, Moussot; Mustapha, Benkhalifa; Rosalie, Cabry; Brigitte, Gubler; Hafida, Khorsi-Cauet; Moncef, Benkhalifa (Frontiers in Physiology, 2022)
Growth hormone (GH) has gained attention as an anti-aging compound enhancing oocyte quality. In fact, GH is known to activate intrafollicular metabolic events for oocyte maturation. Insulin growth factor I (IGF-I) is another ovarian growth factors that mediate the FSH and GH actions. Cytokines could also increase IVF outcomes. Indeed, IL-6 is a pleiotropic cytokine with multiple cellular effects that can vary based on the physiological environment. IL-6 may also play an important role in follicular development [6]. Clinical studies have been performed to explore the potential role of IL-6 in human oocyte maturation and subsequent embryonic development. To date, the answers are not conclusive. During peri-implantation, many cytokines balances are regulated like pro-inflammatory and anti-inflammatory interleukins. The pro-inflammatory properties of IL-17 and its impact on tumor microenvironment or autoimmune diseases are characterized but new dimensions of IL-17 activity that promotes embryo implantation are not well explored. In the search for answers, our study compared concentrations of growth factors: IGF-1, GH and interleukins: IL-6, IL-17 in follicular fluid (FF) from 140 women divided into two groups depending on bad(G1) or good prognosis(G2) and investigated the relationships between these FF components levels and the main parameters of IVF. GH, IGF-1 and IL-6 were significantly higher for G2. For GH, it was negatively correlated to patient age and positively correlated to maturity rate and to IGF-1. Moreover, GH and IGF-1 were correlated to top embryos rate and cumulative pregnancy rate. Regarding IL-6, it was correlated to IGF-1 level, endometer thickness and implantation rate. As for IL-17, it was only correlated to IL-6. Consequently, all these FF components were predictive of oocyte quality excepting IL-17. GH seemed to be the best biomarker of this quality.